THE SPECTRAL AND PHOTOMETRICAL STUDY OF THE NOVA V1494 AQL = 1999 N2 in 2003 - 2006 yrs - Tkachenko, S. S.; Pavlenko, E. P.; Goranskij, V. P. (Одеські астрономічні публікації, 2017)
Nova V1494 Aql 1999 N2 - one from bright Novas the gone century, in the maximum she was the star of 6th star magnitudes. The spectroscopy observations of 2005 showed the presence of emission lines of the Balmer series, PE II, N IV, O I, [01], O II, O V, N II, characteristic for Nova shells. Some profiles of emission lines have a difficult structure. Profile Hα from data of 2005 has six components that correspond to radial speeds from 200 to 1100 km/c. The spectrum of Nova reflects the extremely heterogeneous structure of shell that broadly speaking shows by itself the structure of type a "equatorial torus - arctic rings / caps ".